USING GAMES TO IMPROVE ENGLISH LANGUAGE TEACHING - Hamrayeva Durdona Farhod qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
In  recent  years,  the  use  of  games  in  English  language  teaching  has  gained significant attention as an effective pedagogical tool. Games create an engaging and motivating learning environment that encourages active participation and meaningful communication among learners. This article examines the role of games in improving English language teaching, focusing on their impact on learners’ motivation, language skills development, and classroom interaction. The study analyzes different types of games used in English language teaching and discusses their pedagogical benefits. The findings  indicate  that  game-based  learning  enhances  learners’  motivation,  reduces anxiety, and improves overall language proficiency. The article also offers practical implications for English teachers.